Causal relationships between type 2 diabetes, glycemic traits and keratoconus - Zhu, Xueying; Cheng, Dan; Ruan, Kaiming; Shen, Meixiao; Ye, Yufeng (Frontiers in Medicine, 2023)
The relationship between diabetes mellitus and keratoconus remains controversial. This study aimed to assess the potential causal relationships among type 2 diabetes, glycemic traits, and the risk of keratoconus.We used a two-sample Mendelian randomization (MR) design based on genome-wide association summary statistics. Fasting glucose, proinsulin levels, adiponectin, hemoglobin A1c (HbA1c) and type 2 diabetes with and without body mass index (BMI) adjustment were used as exposures and keratoconus was used as the outcome. MR analysis was performed using the inverse-variance weighted method, MR-Egger regression method, weighted-mode method, weighted median method and the MR-Pleiotropy Residual Sum and Outlier test (PRESSO).Results showed that genetically predicted lower fasting glucose were significantly associated with a higher risk of keratoconus (IVW: odds ratio [OR]=0.382; 95% confidence interval [CI]=0.261~0.560; P=8.162×10 -7 ). Genetically predicted lower proinsulin levels were potentially linked to a higher risk of keratoconus (IVW: OR=0.739; 95% CI=0.568~0.963; P = 0.025). In addition, genetically predicted type 2 diabetes negatively correlated with keratoconus